Critical Evaluation of Application Porting in Mobile Platforms - Madadipouya, K. (Journal of Engineering and Technology (JET), 2015)
Smart phone has become increasingly popular and sales numbers from the third quarter of 2010 reported that an estimated 80.5 million smart phones were sold worldwide. The statistics expresses that mobile applications have grown significantly and mobile devices have become a part of the user’s everyday life. As companies would like to see their mobile applications reaching a broader audience, the demand for porting applications is necessary before or after developing a software product. Software productions should make sure their products can be easily implemented in several environments, since it will allow the product to reach larger parts of the market in a cost-effective way. This becomes increasingly important when the target market is diverse, and is not eminently dominated by one software environment, such as the mobile market. However, the methods for making applications portable are often very unofficial and ad-hoc based with many constraints and difficulties. In this paper, we critically evaluated the current issues of mobile application porting from various angles. Then, we proposed a standard methodology with proper tools and techniques to overcome the difficulties of mobile application porting and increase the portability of mobile applications.